Stress-Buffering Effects of Mindfulness Programming for Adolescents in Schools During Periods of High- and Low-Stress - Emily C. Helminen; Xiaoyan Zhang; Adam J. Clawson; Melissa L. Morton; Emily L. Cary; Samantha E. Sinegar; Pamela Janack; Joshua C. Felver (ECNU Review of Education)
Purpose Stress is a risk factor for poor educational achievement and health. Mindfulness-based programming (MBP) is a viable technology for reducing stress, and Mindful Stress Buffering theory suggests that the benefits of MBP will be most pronounced during periods of high stress. This research details a replication of the MBP “Learning to BREATHE” in a racially diverse urban public high school during a period of relatively low stress (i.e., absence of high-stakes testing). Design/Approach/Methods Five classrooms ( n  = 66) were randomly assigned by classroom to MBP or typical educational programming. Socioemotional attributes were measured pre–post-intervention. Data were contrasted with results from the initial project that occurred during a period of high stress (i.e., the presence of high-stakes testing). Findings Results indicate a failure to replicate significant intervention effects of MBP on socioemotional attributes. Results indicate that the original Felver et al.’s (2019) sample had higher self-reported stress than the current study's sample. Originality/Value These findings provide the first empirical data in support of the Mindful Stress Buffering theory among an adolescent sample, and this has implications for clinicians and researchers interested in utilizing MBP to support the wellbeing of student populations during other periods of high contextual stress (e.g., COVID-19 pandemic).